OVERVIEW ON PILLARS OF ELECTRON-CORRELATION THEORY - Edmond Febrinicko Armay (JURNAL TEKNOSAINS KODEPENA, 2021)
There are four pillars of electron-correlation theory, i.e., configuration interaction (CI), coupled cluster (CC), many-body perturbation theory (MBPT), and many-body Green’s function (MBGF). Starting from the Hartree-Fock (HF) approximation to provide the more accurate approximations, which include the effects of electron-correlation, this article summarizes the pillars.